Geomagnetic insights on an active tectonic contact: Peceneaga-Camena Fault - Besutiu, L.; Orlyuk, M.; Zlagnean, L.; Roments, A.; Atanasiu, L.; Makarenko, I. (Геофизический журнал, 2014)
Highly detailed, very accurate ground magnetic investigations were jointly conducted by Romanian and Ukrainian researchers on a segment of the Peceneaga-Camenas Fault (PCF) in order to reveal the potential of geomagnetic method for active faults investigating. The survey succeeded to outline the PCF track in the area covered by recent sediments, and provide insights on the fault structure and in-depth development. 2D numerical modeling has been employed for interpreting the obtained geomagnetic anomaly. Lateral variations in magnetization, as suggested by the model, reveal the complex geological architecture in the area, hidden by recent deposits. The zero magnetization outlined in the central part of the survey lines has been interpreted in geodynamic terms, as a breccias zone created along PCF track by its active dynamics. С целью оценки возможностей геомагнитного метода при изучении активных разломов совместно с румынскими и украинскими учеными были выполнены высокоточные наземные исследования Печенежско-Каменского разлома (ПКР). Съемка позволила проследить положение ПКР под современными осадочными образованиями и получить представление о его глубинной структуре. Интерпретация выделенных вдоль профилей магнитных аномалий была выполнена с помощью двумерного численного моделирования. В соответствии с моделью, латеральные вариации намагниченности исследуемой зоны свидетельствуют о сложном геологическом строении, скрытом под молодыми осадками. Область коры с нулевой намагниченностью, которая выделена в центральной части геомагнитных профилей, проинтерпретирована с геодинамичеких позиций как пояс брекчированных пород, образованных вдоль ПКР вследствие активных перемещений по нему.